Pengaruh Aplikasi Wattpad dengan Teknik Terbimbing Terhadap Kemampuan Menulis Cerpen Siswa Kelas XI Sekolah Menengah Kejuruan Pertanian dan Pembangunan Cianjur - Husna, Salsa Amaliyatul; Agustiani, Tanti; Suparman, Fauziah (Universitas Islam Sumatera Utara, 2025)
This study aims to examine the effectiveness of using the Wattpad application with guided techniques in improving the short story writing skills of 11th-grade students at the Cianjur Agriculture and Development Vocational School. This research employs a quantitative approach with an experimental research design. Initial observations and pretest results revealed that students’ short story writing skills were still poor, falling into the low category. To address this issue, an intervention was conducted using the Wattpad application as a digital writing medium combined with guided techniques. The posttest results showed a significant improvement in students’ writing performance. Statistical analysis confirmed a substantial increase in scores, with pretest results averaging 43.47 and posttest results increasing to an average of 72.57. The findings indicate that integrating digital platforms like Wattpad with structured guidance can enhance students’ ability to compose short stories effectively.